Letter from the Aviation Advisory Committee to the Federal Aviation Administration July, 1973 - Lewis Simon:::::: (1973)
A letter sent by the Ventura County Aviation Advisory Committee discussing the proposed airport expansion and the opinions of the people of Oxnard.